2013
DOI: 10.1370/afm.1445
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physicians' Use of an Informed Decision-Making Process for Prostate Cancer Screening

Abstract: PURPOSE Leading professional organizations acknowledge the importance of an informed decision-making process for prostate cancer screening. We describe primary care physicians' reports of their prescreening discussions about the potential harms and benefi ts of prostate cancer screening. METHODS Members of the American Academy of Family Physicians NationalResearch Network responded to a survey that included (1) an indicator of practice styles related to discussing harms and benefi ts of prostate-specifi c anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…Study participants were asked to discuss their experiences with the benefits and harms of screening. However, because providers sometimes order tests without discussing them with patients 59 , patients in our study did not always remember receiving screening tests, and thus it is not surprising that some had difficulty discussing their experiences with and perceptions of the benefits and harms of screening. Another limitation is that we asked only about factors affecting screening decisions in the context of four specific screening tests.…”
Section: Discussionmentioning
confidence: 80%
“…Study participants were asked to discuss their experiences with the benefits and harms of screening. However, because providers sometimes order tests without discussing them with patients 59 , patients in our study did not always remember receiving screening tests, and thus it is not surprising that some had difficulty discussing their experiences with and perceptions of the benefits and harms of screening. Another limitation is that we asked only about factors affecting screening decisions in the context of four specific screening tests.…”
Section: Discussionmentioning
confidence: 80%
“…18,19,21,41 Most PSA screening occurs with incomplete or no physician-patient discussion of its associated advantages, disadvantages, and uncertainty. These elements of shared decision making occur at different rates and are associated with different factors, suggesting variation in specific shared decision-making practices for individual patients.…”
Section: Discussionmentioning
confidence: 99%
“…National surveys have shown that many men who undergo PSA screening are poorly informed, and screening decisions are typically made by clinicians alone. [17][18][19][20][21] PSA screening in the absence of shared decision making exposes men to its potential harms without their knowledge and has been a dominant focus of policy debates. 4,17,19,22 The USPSTF's revised guidelines address this problem by not only discouraging routine screening, but recommending that physicians "should not offer or order PSA screening unless they are prepared to engage in shared decision making."…”
Section: Introductionmentioning
confidence: 99%
“…Optimally, urologists' diagnostic approaches should be consistent with German interdisciplinary guidelines and the recently published results of the ERSPC and the PLCO trial. On the other hand, it has to be assumed that most men will initially contact their general practitioner (GP) or internal specialist (IS) for early detection of PCa [7,8,9,10]. Evidence is lacking about the proportion of population-based PCa screening initiated by GPs and ISs.…”
Section: Introductionmentioning
confidence: 99%